2012
DOI: 10.1093/jac/dks049
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characteristics of extended-spectrum-β-lactamase- and AmpC-producing clinical isolates derived from companion animals and horses

Abstract: This is the first study among a large collection of Dutch companion animals and horses characterizing ESBL/AmpC-producing isolates. A similarity in resistance genes and E. coli STs among these isolates and isolates from Dutch poultry and humans may suggest exchange of resistance between different reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 26 publications
7
162
5
1
Order By: Relevance
“…Microbiological investigation revealed isolation of strains of Staphylococcus aureus, Pseudomonas aeruginosa, E.coli, Klebsiella spp., Protius, Bacillus, Clostridium, Streptococcus, Micrococcus and Fusobacterium from different wounds from various species. Our result of bacterial isolation is in support with earlier reports of other workers (Goldstein, 1992;Kelly et al, 1992;Jousmies-Somer et al, 1995;Qureshi et al, 2002;Dierikx et al, 2012;Escobar et al, 2013). In the present study performed over animals for wounds among significant isolates Staphylococcus aureus was the most common isolate (36.22%) followed by E. coli from 34.59 % cases and showed different pattern of sensitivity as evident from the Table 2 and 3.…”
Section: Discussionsupporting
confidence: 92%
“…Microbiological investigation revealed isolation of strains of Staphylococcus aureus, Pseudomonas aeruginosa, E.coli, Klebsiella spp., Protius, Bacillus, Clostridium, Streptococcus, Micrococcus and Fusobacterium from different wounds from various species. Our result of bacterial isolation is in support with earlier reports of other workers (Goldstein, 1992;Kelly et al, 1992;Jousmies-Somer et al, 1995;Qureshi et al, 2002;Dierikx et al, 2012;Escobar et al, 2013). In the present study performed over animals for wounds among significant isolates Staphylococcus aureus was the most common isolate (36.22%) followed by E. coli from 34.59 % cases and showed different pattern of sensitivity as evident from the Table 2 and 3.…”
Section: Discussionsupporting
confidence: 92%
“…A survey carried out in Netherlands in companion animals and horses demonstrated a 2% prevalence of ESBL and AmpC-producing isolates. The same study identified, ESBL producing S. enterica, Proteus miriabilis and Enterobacter cloaceae from urinary, wound, respiratory, abdominal and bone infections (Dierikx et al, 2012). In Germany from six nosocomially infected dogs, OXA-48 type Carbopenamases producing E. coli and K. pneumonia were isolated (Stolle et al, 2013) and in France CTX-M-15 generating K. pneumoniae have been detected from urinary tract infections of dogs and cats (Haenni et al, 2012).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 83%
“…In farm animals, the use of antibiotics that are critically important in human medicine could result in the emergence of new forms of multi-resistant bacteria that infect people. Some new strains of multi-resistant foodborne bacteria, such as Campylobacter, Salmonella and Escherichia coli that produce the ESBL and/or AmpC enzymes that inactivate nearly all beta-lactam antibiotics and the critically important 3rd and 4th generation cephalosporins, have been isolated from meat and faecal samples of farm animals (Dierikx et al, 2012;Iweriebor et al,. 2015b).…”
Section: Acquired Resistance To Vancomycin Is Mediated By Various Genmentioning
confidence: 99%